Fundamentals of aqueous metallurgy - Han, Kenneth N. (Society for Mining, Metallurgy, and Exploration, 2002)
Written as a text for college and graduate-level instruction, this book presents the fundamentals of aqueous metallurgy and its applications in mineral processing operations. The text presents the physicochemical principles of various water-based processes, including interfacial phenomena, hydrometallurgy, and metallurgical kinetics. It is a valuable reference for those studying mineral processing, resource recovery, and the corrosion of metals and alloys. In addition, it's a practical reference for environmental and chemical engineers, chemists, and mineral processing engineers who are respon.